Oligomerization of Family B GPCRs: Exploration in Inter-Family Oligomer Formation - Ng, Hans K. H.; Chow, Billy K. C. (Frontiers in Endocrinology, 2015)
G protein-coupled receptors (GPCRs) are classified into A to F subfamilies in which only families A, B and C are present in mammals. Some of these GPCRs were found to form higher ordered structures such as oligomers with the discovery of interacting receptors in the form of homomers or heteromers. The importance of these oligomers on regulating receptor functions has recently been an intense research focus. It has been proposed that receptor oligomer formation has impact on its physiological importance on receptor trafficking, signaling, ligand-related regulation, and also is related to certain diseases. The present body of knowledge, however, comprises of mainly intra-family oligomers formation and their consequences. Inter-family oligomers are recognized but there is limited information. This article aims to provide a current view regarding inter-family GPCR oligomerization in the subfamilies A, B and C found in mammals.